Cross-Layer Design pada Wireless Multimedia Sensor Network berbasis EDCA dan H.264/SVC - Emansa Hasri Putra (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
A new approach in transmission of multimedia application over Wireless Sensor Network (WSN) has developed new technologie, Wireless Multimedia Sensor Network (WMSN). However, multimedia data including audio, video, images and scalar data requires different Quality of Service based on the application. This research proposes a new approach based on cross-layer design concept using H.264/SVC and IEEE 802.11e/EDCA standard to optimize the existing protocols. The result shows that video applications can obtain bandwidth and packets end-to-end delay based on Quality of Service requirement during the transmission process over WMSN. Hence, the cross-layer design concept succeeded in optimizing the video transmission over WMSN.